An electrochemiluminescence immunosensor based on ABEI and FCA functionalized Platinum@Copper hierarchical trigonal bipyramid nanoframes. (20th September 2016) - Yang, Huiyun; Wang, Haijun; Xiong, Chengyi; Liu, Yuting; Yuan, Ruo; Chai, Yaqin
Abstract: In this work, an electrochemiluminescence (ECL) immunosensor for ultrasensitive detection of mucin-1 (MUC1) was designed with N-(aminobutyl)-N-(ethylisoluminol) (ABEI) and host-guest inclusion functionalized Platinum@Copperhierarchicaltrigonalbipyramidnanoframes(Pt@Cu HNFs) as signal label. At First, Pt@Cu HNFs were prepared to load abundant amine-modified β-cyclodextrin (β-CD) and luminophore ABEI via Pt-N bond. Based on the effect of host-guest recognition, ferrocenecarboxylic acid (FCA) as a catalyst of ABEI-H2 O2 system was linked on the cavity of amine-modified β-CD to form nanocomposite of Pt@Cu HNFs-ABEI-(β-CD-FCA). Both Pt@Cu HNFs and FCA could catalyze H2 O2 decomposition, which significantly enhanced the ECL intensity of ABEI-H2 O2 system. Forthermore, simultaneously immobilizing ABEI and its catalyst FCA on Pt@Cu HNFs with good electrical conductivity could greatly increase the electron transfer efficiency in the ECL reaction, leading to a further signal amplification. Then, due to its good biocompatibility, large specific surface area and high luminous efficiency, the obtained Pt@Cu HNFs-ABEI-(β-CD-FCA) could act as an ideal nanocarrier of detection antibody (Ab2 ). As a result, a desirable "signal-on" ECL immunosensor was proposed for the detection of MUC1 with a wide linear range from 1 × 10 −5  ng mL −1 to 10 ng mL −1 and a relatively low detection limit of 3.3 fg mL −1 (S N −1  = 3), making this approach hold great potential for protein analysis.